Diagnosing, special education, and ‘learnification’ in Danish schools - Bjørn Hamre (Nordic Journal of Social Research)
This article focuses on a discussion of diagnosing, special education, and ‘learnification’ in a Danish school context in which the increasing use of diagnosis is analysed as resulting from the ideas of normality that are associated with the construction of the pupil as a learner. I argue that diagnosis in schools can be seen as the shadow side of the articulation and management of learning through schools’ requirements for pupils. This article is based on my analysis of files produced by educational psychologists. Learning and diagnosis, I argue, constitute two different, but parallel, ways of looking at being a pupil in school, each of which represents conceptions of deviance and normality. The article’s methodological point of departure draws on a Foucauldian-influenced analysis of diagnosing and learning in education.